Study of in-vitro anti typhoid activity of various roots extracts of Decalepis hamiltonii (Wight & Arn.) - K.V, Kumuda (International Journal of Pharmaceutical & Biological Archive, 2011)
Decalepis hamiltonii is an endangered medicinal plant having various activities and used to treat number of ailments. The present study is an attempt to investigate the action of various extracts of D. hamiltonii tuberous roots against typhoid causing organisms. The powdered roots were extracted with various solvents viz., petroleum ether, chloroform, and ethyl acetate by Soxhlet extraction method and the extracts were tested on typhoid causing organisms. Among these, extracts of petroleum ether and chloroform showed a significant activity against S. Typhi (ATCC 14028), S. paratyphi A and S. paratyphi B respectively on comparison with Ciprofloxacin.